ANALYSIS OF THE LEVEL SATISFACTION INDEPENDENT PARTICIPANTS AND MANAGEMENT OF BPJS KESEHATAN CONTRIBUTION COLLECTABILITY - Surahmawati, Surahmawati; Adnan, Yudi; Karini, Tri Addya; Nur Rahmah (Universitas Islam Negeri Alauddin Makassar, 2024)
Background: The problem that is most often heard in both mass and electronic media is related to the BPJS Health budget deficit. One of the causes is arrears from participants. Objective: This study aims to examine the satisfaction of independent participants and the level of collectibility of BPJS Health contributions with a focus on service quality, the amount of contributions, life satisfaction, satisfaction with the level of collectibility and the amount of premiums, life satisfaction, perceptions of service quality on participant satisfaction. Method: This type of research is associative using quantitative research methods with a sample of 21 people, taken using accidental sampling Result: The research results show that regarding the perception of quality of service access, the results of the T Test on the PLS output show a t-count value (1.059) < t-table (1.725), the amount of contributions from the T Test results on the PLS output shows a t-count value (0.072) < t-table (1.725), participant life satisfaction. T-test results on PLS output show t-count value (0.128) < t-table (1.725), perception of Access Quality. T-test results on PLS output show t-count value (0.061) < t- table (1.725), the premium amount. The T Test results on the PLS output show the t-count value (0.128) < t-table (1.725), the life satisfaction of participants from the T Test results on the PLS output shows the t-count value (1.630) < t-table (1.725), participant satisfaction with the T Test results on the PLS output shows the t-count value (0.103) < t-table (1.725) meaning that all hypotheses are accepted. Conclusion: The conclusion of this research is that the perception of the quality of service access, the amount of contributions, participant life satisfaction and participant satisfaction have a positive influence on the level of collectibility. Perceived quality of service access, premium amount, participant life satisfaction have a positive influence on participant satisfaction.